Magnetic ground states of honeycomb lattice Wigner crystals - Nitin Kaushal; Nicolás Morales-Durán; Allan H. MacDonald; Elbio Dagotto (Communications Physics, 2022)
Flat bands in twisted transition metal dichalcogenide semiconductors can host a wide array of strongly correlated states of matter. Here, the authors theoretically identify a rich phase diagram of charge-ordered states with exotic magnetic ordering emerging in a new class of honeycomb Moiré superlattices.